PEMODELAN PABRIK UNTUK PENGELOLAAN LINI PRODUKSI - Santoso , Budi
Abstract : Nowadays manufacturing industry competition charged to every company must be able to adapt their fast growth in technology or their resources to bargain others in global market. Also consumer's requirement have been diversity and it can be anticipated by every company. To anticipate it can be using an independent production system such as ADiMS (Autonomous Distributed Manufacturing System). Production line control is an answer in order to win this competition era. This case study is based on car demand with 1300 capacity especially passenger car type which its demand has increased more and this need maximally company capability in order to meet with their existing resources. In this research will apply ADiMS with focused in making model of production control especially on body shop line. All of production elements that already exist on body shop line determined as autonomy and to complete model which will be created in this research ensured to use object oriented model method.